2012
DOI: 10.1371/journal.pone.0049462
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Imprinting and Allelic Switching at the DLK1-MEG3 Locus in Human Hepatocellular Carcinoma

Abstract: Deregulation of imprinted genes is an important molecular mechanism contributing to the development of cancer in humans. However, knowledge about imprinting defects in human hepatocellular carcinoma (HCC), the third leading cause of cancer mortality worldwide, is still limited. Therefore, a systematic meta-analysis of the expression of 223 imprinted loci in human HCC was initiated. This screen revealed that the DLK1-MEG3 locus is frequently deregulated in HCC. Deregulation of DLK1 and MEG3 expression accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 44 publications
2
84
0
Order By: Relevance
“…MEG3 is expressed in many human normal tissues, but has failed to express in a variety of human tumour cells, such as non-small cell lung cancer, bladder cancer, prostate cancer and other cancers (9)(10)(11)(12)(13)(14). Additionally, many studies have articulated that MEG3 gene plays an inhibiting role in various tumour cells (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…MEG3 is expressed in many human normal tissues, but has failed to express in a variety of human tumour cells, such as non-small cell lung cancer, bladder cancer, prostate cancer and other cancers (9)(10)(11)(12)(13)(14). Additionally, many studies have articulated that MEG3 gene plays an inhibiting role in various tumour cells (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…MEG3, identified as a member of lncRNAs, is an imprinted gene with maternal expression which encodes a non-coding RNA (10). Dysregulation of MEG3 has been found in various human tumors including hepatocellular carcinoma, renal cell carcinoma and neuroblastoma (11,12). Moreover, MEG3 expression was lost in the majority of clinically non-functioning human pituitary tumors, and it suppressed cancer cell growth, stimulated p53-mediated transcriptional activation, and selectively activated p53 target genes (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the tumor-suppressive effect of MEG3 has been confirmed in vivo and in vitro, and analyzing the accumulation of p53 using Kaplan-Meier analyses and Cox proportional regression deduced that MEG3 promoted HCC cell proliferation and apoptosis. It has been suggested that MEG3 may be a potential biomarker for predicting the survival rate of HCC patients [74] .…”
Section: Maternally Expressed Genementioning
confidence: 99%